STUDENTS IMPROVEMENT IN READING COMPREHENSION THROUGH SURVEY, QUESTION, READ, RECITE, REVIEW (SQ3R) TECHNIQUE - Adla Mileni; Diah Astriyanti; Sahrawi Sahrawi; Heti Susanti (IKIP PGRI Pontianak, 2024)
To improve the reading comprehension of eighth grade students of SMP Muhammadiyah 2 Pontianak in the academic year 2023/2024, this study aimed to apply the SQ3R technique. Using the classroom action research method, qualitative and quantitative approaches were used to analyse individual scores and students' average scores. Judging from the field notes and observation checklist, there was an increase in the aspects that were the focus of this study. The students' reading comprehension test results were analysed quantitatively, showing an increase in the average score from 72 in cycle I to 89 in cycle II. In conclusion, the application of SQ3R has a positive impact in improving students' reading comprehension.